Integrating E-Comic Media in Geography Education: Enhancing Student Understanding of the Hydrosphere's Role in Life Systems - Husain, Al Qomar Nur Mahmud; Soelistijo, Djoko; Masitoh, Ferryati (Future Space: Studies in Geo-Education, 2024)
Enhancing the quality of education can be achieved by incorporating technology and developing engaging media for students. This research focuses on the development of an educational e-comic covering the hydrosphere and its impact on life, using the ADDIE model—specifically, the stages of Analysis, Design, Development, and Implementation (ADDI). Expert validation confirmed the e-comic’s eligibility with an average score of 93%, classifying it as "very suitable" for educational use. Teachers and students from Senior High School Tumpang (Class XI-F, Social 3) participated in a media suitability test, with teachers rating it at 82% and students at 88%, both falling into the "very appropriate" category. An effectiveness test, conducted with students in Class XI-F, yielded a "moderate" gain score, indicating the e-comic as "sufficiently effective" in supporting learning. Thus, this e-comic meets the standards of suitability and effectiveness for teaching the topic "The Influence of the Hydrosphere on Life”.